Application of carbon nanotubes in structural health monitoring of reinforced concrete - Lagason, Patria Hena P.; Antonio, Oscar Victor M. Jr. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
The use of carbon nanotube as a stress-sensing material component in concrete is the focus of this study. The working concept is that the piezo-resistive property of the carbon nanotube results to a linear variation of the change in electrical resistance of the concrete composite with the applied stress on it. This property has been tested and established in previous studies for CNT-cementitious composites. The research extends the concept to concrete and steelreinforced concrete. The investigation will be carried out by preparing carbon nanotube-concrete specimens with parameters and procedures adapted from successful previous researches. The experiment will involve concrete and steel-reinforced concrete beams. The carbon nanotubes are to be dispersed through the introduction of a superplasticizer followed by ultrasonication before with cement. The beams are subject simultaneously to a Third-Point Load Test, Four-Point Probe Test, and strain measurement through the use of strain gauges. It was established in the study that the carbon nanotube network exhibit conductivity inside the concrete and was able to translate applied stresses to change in resistances. A consistent increasing trend in resistivity was found in the middle of the concrete specimen which is similar to the trend of the loading which exhibits piezoresistivity. Moreover, resistivity measurements in the steel-reinforced concrete require special detail. The rebar acts as a capacitor that stores energy. The presence of such blocks direct current which results to alternating current readings. Because of this, the resistivity values are fluctuating. It is pointed out that the rebar must be charged to maximwn capacity in order to stabilize the current. Furthermore, a significant increase of 13.6% and 40% in the flexural and compressive strengths, respectively, were attributed to the addition of carbon nanotubes.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Carbon nanotubes; Reinforced concrete; structural health monitoring